2018
DOI: 10.1021/acs.molpharmaceut.8b00548
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Nanoparticle-Loaded Fenofibrate Exerts Inhibitory Effects on Nonalcoholic Fatty Liver Disease in Mice

Abstract: Polyurethane (PU) nanoparticles are potential drug carriers. We aimed to study the in vitro and in vivo efficacy of biodegradable PU nanoparticles loaded with fenofibrate (FNB-PU) on nonalcoholic fatty liver disease (NAFLD). FNB-PU was prepared by a green process, and its preventive effects on NAFLD were investigated on HepG2 cells and mice. FNB-PU showed sustained in vitro FNB release profile. Compared to FNB crude drug, FNB-PU significantly decreased triglyceride content in HepG2 cells incubated with oleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In recent times, safe, smart, and highly efficient nanomaterials have been gaining importance for their roles in treating different diseases, including NAFLD and dyslipidemia (Wang et al, 2016;Cao et al, 2018;Wan et al, 2018;Lee et al, 2019). Moreover, nanocarriers are promising carriers for gene delivery (Canup et al, 2017;Wang et al, 2018;Zai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, safe, smart, and highly efficient nanomaterials have been gaining importance for their roles in treating different diseases, including NAFLD and dyslipidemia (Wang et al, 2016;Cao et al, 2018;Wan et al, 2018;Lee et al, 2019). Moreover, nanocarriers are promising carriers for gene delivery (Canup et al, 2017;Wang et al, 2018;Zai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In order to explore the effect of NP-RAPA on NAFLD, and compare the therapeutic efficacy, mPEG-PLGA, RAPA, and NP-RAPA were intravenously injected into C57BL/6J mice during the period of HFD feeding (Figure 4). Hematoxylin and eosin (H&E) staining showed that HFD treatment resulted in lipid droplets in the hepatocytes compared with ND-treated mice, indicating the successful establishment of a mouse model of NAFLD, which has been described previously (Cao et al, 2018;Zhao et al, 2018). However, administration of mPEG-PLGA polymers did not induce the reduction in the hepatic lipid accumulation at all.…”
Section: Effects Of Np-rapa On Nafld In Micementioning
confidence: 73%
“…In vitro release profile can be used to determine whether dissolution of the targeted drug into carrier is enhanced by the novel drug delivery platform (Cao et al, 2018). The release curve of RAPA from NP-RAPA in vitro at pH 5.5 and 7.4 was shown in Figure 2A with zero time corresponding to the start of the incubation period.…”
Section: Drug Loading and Release Profile Of Rapamycin From Np-rapamentioning
confidence: 99%
“…H20030569), which is a peroxisome proliferator-activated receptor- γ (PPAR γ ) agonist used as a positive drug in vivo [ 23 ], was purchased from Chengdu Hengrui Pharmaceutical Co. Ltd. Fenofibrate (FNF) (Lot. S5812), which is a PPAR α agonist used as a positive drug in vitro [ 24 ], was purchased from Selleck Chem, Inc., (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%